The potential value of early (1939–1967) upper‐air data in atmospheric climate reanalysis. (18th May 2017) - Hersbach, Hans; Brönnimann, Stefan; Haimberger, Leopold; Mayer, Michael; Villiger, Leonie; Comeaux, Joey; Simmons, Adrian; Dee, Dick; Jourdain, Sylvie; Peubey, Carole; Poli, Paul; Rayner, Nick; et al.
Abstract : In recent years a number of reanalysis datasets have been published that cover the past century or more, including the 'Twentieth Century Reanalysis' 20CRv2 and the European Reanalysis of the twentieth century ERA‐20C. These datasets are widely used, showing the need for, and possible benefit of, reanalysis data products designed for climate applications. The twentieth‐century reanalyses so far have assimilated only surface observations, and rely on independent estimates of monthly averaged sea‐surface temperatures and sea ice concentrations as boundary conditions. While 20CRv2 uses only observations of surface and sea‐level pressure, ERA‐20C additionally assimilates marine winds. Here we describe an experimental reanalysis, referred to as ERA‐PreSAT, which covers the period 1939–1967 and also assimilates historical upper‐air data. Assessments of this dataset including comparisons with independent data show that (i) temperature biases in the Northern Hemisphere are largely reduced compared to reanalyses that assimilate surface data only, (ii) concentration of 1940s upper‐air data in the northern extratropics created a strong interhemispheric asymmetry which is likely not realistic, (iii) the forecast skill in the Northern Hemisphere has increased substantially compared to reanalyses that assimilate surface data only, (iv) day‐to‐day and (in the northern extratropics) month‐to‐month correlations with independent observations (of total column ozone, upper‐air data) increase over time, (v) interannual variability is well captured in the reanalysis, (vi) a signature of the stratospheric Quasi‐Biennial Oscillation is present as far back as the 1940s, and (vii) tropical cyclones are not well represented. The generally encouraging results from the experimental ERA‐PreSAT reanalysis underline that early upper‐air data greatly contribute to our knowledge on the troposphere and lower stratosphere over the twentieth century. Abstract : Evolution of upper‐air data that were actively assimilated in ERA‐PreSAT per day in 5×5 degree grid boxes, averaged over (from top to bottom) (a, b) 1943, (c, d) 1950, (e, f) 1957 and (g, h) 1964, for (a, c, e, g) upper‐air temperature and (b, d, f, h) wind.